PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING PADA SISTEM PENDUKUNG KEPUTUSAN PENENTUAN BEASISWA DAN REKOMENDASI MAGANG - Dinar Ajeng Kristiyanti (University of Muhammadiyah Tangerang, 2021)
In educational institutions such as universities, scholarships and apprenticeship programs are mandatory, likewise at Trisakti University. Students who receive scholarships must meet predetermined criteria. The problem that often occurs is the provision of scholarships and inappropriate apprenticeship opportunities. The application of the decision support system used is Simple Additive Weighting (SAW) with Multiple Attribute Decision Making (FMADM) is expected to help the university in determining outstanding students who are entitled to receive scholarships and internship recommendations by assessing each student, looking for a weighted addition of the rating performance on each alternative on all attributes. This is useful for making it easier for decision makers related to the problem of selecting outstanding students, so that students who are most worthy of an award will be found in the form of scholarships or recommendations for internships using the criteria for Student Activity Portfolio Aspects, Mastery of English, Creative Ideas Scientific Writing, and National Insights. Based on the results of calculations using the Simple Additive Weighting method by taking into account the existing criteria, students who get the highest score will be selected for scholarships and internship recommendations.